Effect of stacking pattern of multilayered polyetheretherketone/boron nitride composites on the mechanical and thermal properties: Experiments and molecular dynamics simulations - Oh, Yuna; Bae, Kwak Jin; Kim, Yonjig; Yu, Jaesang (Pergamon Press Ltd., 2024)
The effect of stacking patterns in multilayered polyetheretherketone (PEEK)/boron nitride (BN) composites was investigated to improve the thermal conductivity and mechanical properties. The thick PEEK and BN layers in the multilayered composite were the best multilayer structure, resulting in high mechanical properties and in-plane thermal conductivity due to the many strong electrostatic interaction sites between boron nitride nanosheets (BNNSs). Molecular dynamics simulations were used to clarify the enhanced mechanism of multilayered structure on thermal conductivity. The multilayered structure with combinations of PEEKs and thick BN layers composed of large BNNSs led to the optimization of heat transfer due to the effective phonon transfer path. The best multilayered composite had the highest in-plane thermal conductivity, which was 471% higher than that of a PEEK. This study provides information about the filler size and stacking patterns for more effective multilayer structures with polymer and filler layers to achieve high performance on mechanical and thermal properties.